English Vocabulary Learning Application For Students of SD Negeri Cibatu, Tasikmalaya Regency - Laura Laura (Institute of Computer Science (IOCS), 2021)
Teaching that seems conventional can cause students to find it difficult to understand the material presented by the teacher, as a result, student interest in learning will result in a decrease and have an impact on student achievement. Starting from this, learning by using multimedia that uses media elements such as animation, text, and images that are packaged in a container that is interactive, creative, and fun in order to attract students to increase student interest in learning. Based on the aforementioned background, the purpose and benefit of this research is to build an application for learning English vocabulary for elementary school students in grades 1, 2 and 3 using macromedia flash. It is hoped that this learning application can be used as an application that helps teachers in the learning process,